Poetics of Translation, its Ethics and Policy: an Analysis of Translation of A Game of Thrones by George R. R. Martin into Lithuanian and French - Černiuvienė, Liucija (Literatūra, 2016)
The article embarks upon the discrepancy in time between the establishment of the first translation schools in Europe and in Lithuania, where the first translation school dates back as late as the last decades of the twentieth century, after regaining Independence. The historical overview accounts, in a sense, for at times lesser importance of the quality of translation than anticipated. The article aims at a study of Lithuanian and French translations of A Game of Thrones by George R. R. Martin; the novel opens a series of books under the title A Song of Ice and Fire. The analysis is based on Henri Meschonnic’s concepts of poetics of translation, ethics and policies. It also adopts Anthony Pym’s principles of translation ethics. George R.R. Martin’s phenomenon is briefly discussed in the article, his role in the contemporary world of science fiction genre, specifically in the niche of epic fantasy novels is presented. Having discussed concepts of poetics of translation, translation and translator’s ethics, as well as policies of translation, the author procedes with selected samples of French and Lithuanian translations and presents them in problem-based units, such as translation of proper names of the literary characters, metaphorical expressions and literal translation. Having analysed the corpus of samples in Lithuanian and French the author arrives at the conclusion that the translator into French has preserved the poetics of the original and has demonstrated adherence to the principles of translator’s ethics, while the translator into Lithuanian has failed in her attempt to reveal the poetics of the text, and the big number of word-for-word translation passages indicates some lack of fidelity to the original text and its translation, as well as translator’s ethics in general. Thus it may be assumed, from a broader perspective, that the recently established school of translation in Lithuania lacks some tradition of quality as applied to translation text and that may cause such unfortunate results as the study has revealed.